2013
DOI: 10.1007/s11060-013-1219-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of adjuvant radiotherapy in atypical meningioma

Abstract: The object of this study was to analyze treatment outcomes and to identify the prognostic factors, with a focus on the role of adjuvant radiotherapy (ART), predicting disease progression in atypical meningiomas. From 1997 to 2011, 83 patients with meningioma were included in this study. All patients were histologically confirmed as atypical meningioma and were treated with surgical resection with or without ART. As primary therapy, 27 patients received surgical resection followed by ART, and 56 received no adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 15 publications
7
109
1
Order By: Relevance
“…Clinically, recurrence rates vary between studies, depending on both the duration of follow-up and the number of patients studied. An analysis of some of these studies has shown that the patient's age at diagnosis, 20 complete resection or GTR, 30 and postoperative radiotherapy 20,33 are invariably associated with lower risks of atypical meningioma recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, recurrence rates vary between studies, depending on both the duration of follow-up and the number of patients studied. An analysis of some of these studies has shown that the patient's age at diagnosis, 20 complete resection or GTR, 30 and postoperative radiotherapy 20,33 are invariably associated with lower risks of atypical meningioma recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 83 patients of whom 66% had undergone GTR, Park et al reported a 5-year tumor control of 59% versus 44% with and without postoperative RT, respectively 72 . Improved progression-free survival rates after postoperative RT have been observed in comparative retrospective series [73][74][75] .…”
Section: Extent Of Resection (Eor) As Iis Defined By the Simpsonmentioning
confidence: 99%
“…2,3,45 These studies reported improved LC or a trend toward improved LC with adjuvant EBRT and GTR versus GTR alone (p = 0.04, p = 0.09, and p = 0.10; tine adjuvant EBRT after GTR (Table 3). 13,24,26,37,46,48,59,78,81,85 Eight of these 10 studies did not detect any significant improvement in PFS with adjuvant EBRT, and the remaining 2 studies did not detect any significant improvement in LC. The discrepancy between these and the aforementioned 3 studies may in part be due to the categorization of less intrinsically aggressive or more radiation-resistant meningiomas as 2000/2007 WHO AMs compared with the 1993 WHO criteria.…”
Section: Adjuvant Ebrt After Gtrmentioning
confidence: 99%
“…The 5-year PFS after GTR is 59%-90% but the 5-year PFS after subtotal resection (STR) is only 30%-70% (Table 2). 13,24,26,46,48,59,77,78,81,85,87 For each of these studies, GTR shows a significant benefit over STR or Simpson Grade IV resection for AMs (EBM Level 3, Grade 1C recommendation). However, "maximal safe resection" may be a more appropriate strategy than GTR, given the surgical morbidity associated with resection in certain locations (e.g., cavernous sinus).…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation